Ergonomic Evaluation of Portable Dining Furniture and Spatial Layout at Gultik Street, Taman Labuai Citywalk, Pekanbaru - Achnia Tiffany Nurfadillah; Muhammad Rasyidul Ilmi; Musyaffa Rifqi Harimardika; Intan Agustina Pratiwi; Hannisa Handri (Jurnal Koridor, 2026)
Public spaces foster social interaction and support culinary micro, small, and medium enterprises (UMKM) that rely on accessible settings. Taman Labuai Citywalk in Pekanbaru is one such space where tenants, including Gultik Street, use portable dining furniture. Variations in furniture types and dimensions can lead to different levels of user comfort. This study evaluates the ergonomic suitability of dining furniture and the spatial layout at Gultik Street to assess comfort in an outdoor dining context. A descriptive qualitative approach was applied through direct observation, documentation, and on-site measurement of four table types and five chair types. Dimensions were compared with anthropometric and ergonomic references from Neufert (1996) and Dartfort (1990). Only a few items (e.g., the black chair with a backrest, the blue metal chair, and several dining tables) matched the recommended ranges. Plastic chairs, camping chairs, and bar stools did not, mainly due to unsuitable seat height, limited seat size, and insufficient back support, which may reduce comfort during prolonged sitting. Although the layout is flexible and can adjust to visitor numbers, circulation becomes constrained at peak hours and may reduce overall comfort. The findings emphasize selecting ergonomically compliant furniture and providing adequate circulation space in outdoor public dining areas